Structural insights into brassinosteroid export mediated by the Arabidopsis ABC transporter ABCB1 - Wei, H; Zhu, H; Ying, W; Janssens, H; Kvasnica, M; Winne, JM; Gao, Y; Friml, Jiří; Ma, Q; Tan, S; Liu, X; Russinova, E; et al. (Plant Communications)
Brassinosteroids (BRs) are steroidal phytohormones indispensable for plant growth, development, and responses to environmental stresses. The export of bioactive BRs to the apoplast is essential for BR signalling initiation, which requires binding of BR molecule to the extracellular domains of the plasma membrane-localized receptor complex. We have previously shown that the Arabidopsis thaliana ATP-binding cassette (ABC) transporter, ABCB19, functions as a BR exporter, and together with its close homologue, ABCB1, positively regulate BR signalling. Here, we demonstrate that ABCB1 is another BR transporter. The ATP hydrolysis activity of ABCB1 was stimulated by bioactive BRs, and its transport activity was confirmed in proteoliposomes and protoplasts. Structures of ABCB1 in substrate-unbound (apo), brassinolide (BL)-bound, and ATP plus BL-bound states were determined. In the BL-bound structure, BL was bound to the hydrophobic cavity formed by the transmembrane domain, and triggered local conformational changes. Together, our data provide additional insights into the ABC transporter-mediated BR export.

Divergence of trafficking and polarization mechanisms for PIN auxin transporters during land plant evolution - Tang, Han; Lu, KJ; Zhang, Y; Cheng, YL; Tu, SL; Friml, Jiří (Plant Communications)
The phytohormone auxin and its directional transport through tissues play a fundamental role in development of higher plants. This polar auxin transport predominantly relies on PIN-FORMED (PIN) auxin exporters. Hence, PIN polarization is crucial for development, but its evolution during the rise of morphological complexity in land plants remains unclear. Here, we performed a cross-species investigation by observing the trafficking and localization of endogenous and exogenous PINs in two bryophytes, Physcomitrium patens and Marchantia polymorpha, and in the flowering plant Arabidopsis thaliana. We confirmed that the GFP fusion did not compromise the auxin export function of all examined PINs by using radioactive auxin export assay and by observing the phenotypic changes in transgenic bryophytes. Endogenous PINs polarize to filamentous apices, while exogenous Arabidopsis PINs distribute symmetrically on the membrane in both bryophytes. In Arabidopsis root epidermis, bryophytic PINs show no defined polarity. Pharmacological interference revealed a strong cytoskeleton dependence of bryophytic but not Arabidopsis PIN polarization. The divergence of PIN polarization and trafficking is also observed within the bryophyte clade and between tissues of individual species. These results collectively reveal a divergence of PIN trafficking and polarity mechanisms throughout land plant evolution and a co-evolution of PIN sequence-based and cell-based polarity mechanisms.

TOPLESS promotes plant immunity by repressing auxin signaling and is targeted by the fungal effector Naked1 - Navarrete, Fernando; Gallei, Michelle C; Kornienko, Aleksandra E.; Saado, Indira; Khan, Mamoona; Chia, Khong-Sam; Darino, Martin A.; Bindics, Janos; Djamei, Armin (Plant Communications)
In plants, the antagonism between growth and defense is hardwired by hormonal signaling. The perception of pathogen-associated molecular patterns (PAMPs) from invading microorganisms inhibits auxin signaling and plant growth. Conversely, pathogens manipulate auxin signaling to promote disease, but how this hormone inhibits immunity is not fully understood. Ustilago maydis is a maize pathogen that induces auxin signaling in its host. We characterized a U. maydis effector protein, Naked1 (Nkd1), that is translocated into the host nucleus. Through its native ethylene-responsive element binding factor-associated amphiphilic repression (EAR) motif, Nkd1 binds to the transcriptional co-repressors TOPLESS/TOPLESS-related (TPL/TPRs) and prevents the recruitment of a transcriptional repressor involved in hormonal signaling, leading to the de-repression of auxin and jasmonate signaling and thereby promoting susceptibility to (hemi)biotrophic pathogens. A moderate upregulation of auxin signaling inhibits the PAMP-triggered reactive oxygen species (ROS) burst, an early defense response. Thus, our findings establish a clear mechanism for auxin-induced pathogen susceptibility. Engineered Nkd1 variants with increased expression or increased EAR-mediated TPL/TPR binding trigger typical salicylic-acid-mediated defense reactions, leading to pathogen resistance. This implies that moderate binding of Nkd1 to TPL is a result of a balancing evolutionary selection process to enable TPL manipulation while avoiding host recognition.

All roads lead to auxin: Post-translational regulation of auxin transport by multiple hormonal pathways - Semeradova, Hana; Montesinos López, Juan C; Benková, Eva (Plant Communications)
Auxin is a key hormonal regulator, that governs plant growth and development in concert with other hormonal pathways. The unique feature of auxin is its polar, cell-to-cell transport that leads to the formation of local auxin maxima and gradients, which coordinate initiation and patterning of plant organs. The molecular machinery mediating polar auxin transport is one of the important points of interaction with other hormones. Multiple hormonal pathways converge at the regulation of auxin transport and form a regulatory network that integrates various developmental and environmental inputs to steer plant development. In this review, we discuss recent advances in understanding the mechanisms that underlie regulation of polar auxin transport by multiple hormonal pathways. Specifically, we focus on the post-translational mechanisms that contribute to fine-tuning of the abundance and polarity of auxin transporters at the plasma membrane and thereby enable rapid modification of the auxin flow to coordinate plant growth and development.